Enterprise Risk Management and Performance of Insurance Companies (The Lumbini Journal of Business and Economics, 2024)
Purpose: This research aims to investigate the impact of risk identification (RI), risk assessment (RA), risk mitigation (RM), and risk management (RMG) on institutional performance (IP). The objective is to analyze both individual and combined effects of these risk management practices on institutional outcomes.Methods: The study used descriptive and causal research design. The data were collected using structured questionnaire with five-point likert scale, targeting 151 managers, officers, and department heads from both life and non-life insurance sectors from Rupendehi district. The correlation analysis was used to examine the relationships between variables and Stepwise regression analysis to explore the effect.Results: It reveals that RA, RM and RMG had significant positive effect on institutional performance at individual level. When they are analyzed in single model RA and RM were only found significant. RI, while consistently positive, was found to be statistically insignificant across all models. RA and RM are significant variables of institutional performance, while RI and RMG play lesser roles.Conclusion: it is necessary to acquire deeper understanding on how risk management practices enhance institutional outcomes.